Análise de relacionamentos interorganizacionais: um estudo a luz da Teoria dos Custos de Transação (Management and Connections Journal, 2020)
The study analyzes the attributes of relationship management between hotels and food suppliers in light of the Transaction Cost Theory. This is an empirical research on the perception of hotel managers regarding the selection of food suppliers and the commercial relationship to ensure the supply of food needed for guest service. The methodological approach considers the complementarity between the qualitative and the quantitative method. Eighteen hotel managers were interviewed in the Belem Metropolitan Region; among these seven were in-depth interviews. The survey results show that: there is a preference for market governance; the power of hotels is reinforced by the definition of norms and rules of relationship; transaction support is anchored in collaborative actions, timely payment, and frequency of transactions that help eliminate opportunistic behavior, reduce uncertainty, and reduce transaction costs.